Authenticated secret session key using elliptic curve digital signature algorithm. Issue 2 (27th January 2021) - Mehibel, Nissa; Hamadouche, M'hamed
Abstract: Elliptic curve Diffie‐Hellman (ECDH) scheme is the basic key exchange used in elliptic curve cryptography. ECDH is a public key cryptosystem based on the discrete logarithm problem, but is vulnerable to man‐in‐the‐middle attack because it does not authenticate the secret session key. The integration of the elliptic curve digital signature allows authenticating the secret session key of the ECDH scheme (A‐ECDH). However, it is a technique (A‐ECDH) that uses a single random variable and it has been shown in the literature that a single random variable does not make the system secure. Therefore, the use of two random variables has been suggested to secure an authentication scheme. In this paper, a new authentication scheme using the elliptic curve digital signature algorithm is proposed. The performance analysis of the proposed authentication protocol is performed. The comparative results from the perspective of security and computation time showed that the proposed authentication protocol is more efficient in terms of computation time compared to the related works and it provides all the security features.